Inflammatory biomarkers in Alzheimer’s disease - Barra, Cátia Isabel de Almeida (2018)
Alzheimer’s disease (AD) is the most common form of dementia. Histopathologically it is characterized by the presence of two major hallmarks, the intracellular neurofibrillary tangles (NFT) and the extracellular senile plaques (SP), which are surrounded by activated astrocytes and microglia. Neuroinflammation has been associated with some neurodegenerative diseases. In AD the inflammatory process, prompted by increased Aβ production and aggregation, was reported to have a fundamental role in disease pathogenesis. In early stages the inflammation could have a beneficial role in the pathology, since it has been proposed that the microglia and astrocytes activated could be involved in (amyloid β) Aβ clearance. Nevertheless, the chronic activation of the microglia leads to excessive production of the inflammatory components, including cytokines. It promotes alterations in amyloid precursor protein (APP) expression and processing, stimulating the increase of Aβ accumulation, abnormal Tau phosphorylation and, consequently, neurotoxic effects, irreversible damage and loss of neurons. Since chronic neuroinflammation is a feature of AD, inflammatory proteins may constitute potential biomarkers candidates to assist clinical diagnosis of this dementia. Thus, the main aim of this study was to identify putative inflammatory biomarkers for AD by flow citometry analysis. For plasma samples of individuals examined by clinical dementia rating (CDR) and mini mental (MM) diagnostic tests were used. Subjects were subdivided in 3 distinct groups, a control group (CDR-/MM-) and two patient groups, CDR+/MM- and CRD+/MM+, the former may include mild cognitive impairment (MCI) patients and the latest group included 5 patients clinical diagnosed as AD. Data analysis revealed differences in the inflammatory proteins levels of both patients groups (CDR+/MM- and CDR+/MM+) in comparison to healthy individuals (CDR-/MM-). Interleukin-8 (IL-8) plasma levels were statistically different (P<0,05) from control group. Significant correlation between IL-8 concentrations and the CDR stages was also identified. Additionally, correlations of monocyte chemoattractant protein-1 (MCP-1) with both IL-8 and IL-6 were observed. Taken together these findings suggested that IL-8 could be a potential biomarker not only for AD but also for diagnosis of initial stages of dementia.